Nuclear energy as environmentally friendly energy and international politics - Ali Bogheiry; Ai Ahmad Faisal; Sunarno Sunarno (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The growth of the world's human population demands greater energy fulfillment and the main energy source that has been used so far is fossil fuels. Nuclear energy produced in a nuclear reactor is used as a competitive contributor with other sources of electrical energy such as coal, oil, gas, water, and others. So that the contribution of energy from various aspects becomes something that must be taken as a mutually beneficial strategic partner in meeting future energy needs that are economical and environmentally friendly at both national and international levels. The result of this research is energy is a primary need in modern human life. Almost all aspects of life require energy as its prime mover. In the beginning, people used fossil energy to fulfill their needs. The limited amount of fossil energy on earth has resulted in many people competing to create renewable energy with the characteristics of low cost, high stability, and high efficiency. Energy savings are urgent to be done so that the nation can survive in the midst of a crisis like this. In addition, this is also a warning that excessive dependence on fossil energy sources or primary energy such as oil, coal and natural gas is not a good option. Modern energy sources include solar energy, nuclear energy, wind energy, hydro energy, geothermal energy, biomass energy, hydrogen fuel cell energy, and biofuel energy. So that in the development of nuclear energy, treaty rules are made and there is international law in it. This is done so that every country in developing its nuclear energy still maintains international peace and security.